2011
DOI: 10.1002/art.30344
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of anti-signal recognition particle autoantibody levels with creatine kinase activity in patients with necrotizing myopathy

Abstract: Objective. Anti-signal recognition particle (anti-SRP) autoantibodies are associated with severe acquired necrotizing myopathies. The role of these autoantibodies remains elusive, and the evolution of anti-SRP levels over time is unknown. In this study, we developed an addressable laser bead immunoassay (ALBIA) technique to investigate a correlation between anti-SRP levels, serum creatine kinase (CK) levels, and muscle strength in patients with necrotizing myopathy.Methods. The diagnostic value of the ALBIA as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
140
3
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(161 citation statements)
references
References 43 publications
(32 reference statements)
7
140
3
11
Order By: Relevance
“…In contrast, the connective-tissue disease associated patients had relatively preserved power and lower CK levels. These findings are all consistent with previous studies, with the anti-SRP subgroup tending to have the most severe weakness and statin-naïve anti-HMGCR positive patients having CK levels disproportionately high for the weakness severity (1,16,18). Our entire cohort received serological testing and all but one patient had a muscle biopsy performed, with only four patients without either positive anti-SRP or anti-HMGCR serology.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, the connective-tissue disease associated patients had relatively preserved power and lower CK levels. These findings are all consistent with previous studies, with the anti-SRP subgroup tending to have the most severe weakness and statin-naïve anti-HMGCR positive patients having CK levels disproportionately high for the weakness severity (1,16,18). Our entire cohort received serological testing and all but one patient had a muscle biopsy performed, with only four patients without either positive anti-SRP or anti-HMGCR serology.…”
Section: Discussionsupporting
confidence: 90%
“…This supports the recently published diagnostic algorithm by Mammen et al, [14] which recommends serological testing for anti-HMGCR antibodies prior to muscle biopsy. Given the specificity of positive anti-HMGCR antibodies for NAM in the context of patients over 50 years with previous stain exposure [6,18,19], perhaps future diagnoses could be based on clinical picture and serology alone, without the need for invasive muscle biopsies. All patients were screened clinically for malignancy and 40% of our cohort received formal malignancy screening including either PET or CT imaging of chest, abdomen, pelvis, although no patients were found to have malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, expression of serum SRP is extensively researched in both domestic and international studies (Benveniste et al, 2011;Fernandez et al, 2013;Hanisch et al, 2013;Wang et al, 2014). It has been demonstrated that serum anti-SRP antibody is closely associated with autoimmune necrotizing myopathy (Picard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that anti-SRP19 antibody expression in muscle tissue of autoimmune NM patients has no apparent association with patient gender, age, duration, tension, creatine kinase, and other myositis-related antibodies. Benveniste et al (2011) quantitatively measured the level of anti-SRP antibodies in 8 cases of anti-SRP antibody-positive patients before and after glucocorticoid and immunosuppressive therapy, and found that serum CK and anti-SRP antibody concentrations decreased with improved symptoms before and after treatments (Stone et al, 2007;Mohassel and Mammen, 2013). Recent studies have confirmed that improvement of symptoms and remission of necrotizing myopathy is associated with returning of anti-SRP antibody to normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-SRP subjects have unique clinical features, including more severe myopathy with dysphagia, very high CK levels, and better response to steroid therapy [3] . Two recent case series have suggested that anti-SRP levels do correlate with disease severity, and may serve as a marker of poor prognosis [13,14] . Additionally, a recent study identified anti-HMGCoA reductase autoantibodies in 63% of patients with necrotizing autoimmune myopathy [15] .…”
Section: Discussionmentioning
confidence: 99%